THE STUDY OF RESIDUAL TOXIC SPILLS OF GASOLINE FRACTIONS BY THE BIOTESTING - Zelenko, Yu. V. (Science and Transport Progress, 2008)
To develop further recommendations on the use of phytoremediation process for final cleaning of soils from light fractions of petroleum products the residual phytotoxicity of soils contaminated with petrol fractions has been studied.